Riskr: a web 2.0 platform to monitor and share disaster information. (2015) - Farber, Jess; Myers, Trina; Trevathan, Jarrod; Atkinson, Ian; Andersen, Trevor
Disaster management that uses web-based technology to enhance user collaboration around disasters is an emergent field. A number of dedicated 'disaster portals' exist but they do not integrate large social networks such as Twitter and Facebook. These social networking sites can facilitate the analysis and sharing of collective intelligence around disaster information on a far greater scale by increasing accessibility to, and the use of, a disaster portal. This paper presents the 'Riskr' project, which applies a low-technological solution to creating a disaster portal fed by social networking messages. The system has been implemented using Twitter and tested by users to determine the feasibility. Results suggest the combination of online services and interoperability between disaster portals; and social networks can further enhance disaster management initiatives as 70.5% of the users were able to estimate the correct location of a disaster (e.g. fallen power lines, fire).